ANALISIS THE FIVE FORCES STRATEGY PADA AL-MUMTAZ PEDULI PONTIANAK - Ichsan Iqbal (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2016)
This study discussed the implementation of the strategy management system on zakat management organizations 'Al-Mumtaz Peduli’ Pontianak, West Kalimantan. Using the Five Forces Strategy analysis, the researcher will see to what extent Al-Mumtaz Peduli Pontianak is able to serve its function as a zakat agency competing with other organizations. This study was a field and qualitative research. The data had been obtained through interviews and documentation. This study concludes that Al-Mumtaz Peduli recognized other zakat institutions are partners that can work together to alleviate poverty and social problems. Al-Mumtaz gives services on orphans and wish every village has a religious preacher. Al-Mumtaz Peduli always do a socialization through seminars, mass and electronic media. Relating with collection and distribution of ZISWAF funds, Al-Mumtaz always improves its services to muzaki by giving activity and financial reports socialized by a per-three months’ magazines.